Attenuation of Replication Stress–Induced Premature Cellular Senescence to Assess Anti‐Aging Modalities. Issue 1 (1st July 2014) - Zhao, Hong; Darzynkiewicz, Zbigniew
Abstract: Described is an in vitro model of premature senescence in pulmonary adenocarcinoma A549 cells induced by persistent DNA replication stress in response to treatment with the DNA damaging drug mitoxantrone (Mxt). The degree of cellular senescence, based on characteristic changes in cell morphology, is measured by laser scanning cytometry. Specifically, the flattening of cells grown on slides (considered the hallmark of cellular senescence) is measured as the decline in local intensity of DNA‐associated DAPI fluorescence (represented by maximal pixels). This change is paralleled by an increase in nuclear area. Thus, the ratio of mean intensity of maximal pixels to nuclear area provides a very sensitive morphometric biomarker for the degree of senescence. This analysis is combined with immunocytochemical detection of senescence markers, such as overexpression of cyclin kinase inhibitors (e.g., p21 WAF1 ) and phosphorylation of ribosomal protein S6 (rpS6), a key marker associated with aging/senescence that is detected using a phospho‐specific antibody. These biomarker indices are presented in quantitative terms defined as a senescence index (SI), which is the fraction of the marker in test cultures relative to the same marker in exponentially growing control cultures. This system can be used to evaluate the anti‐aging potential of test agents by assessing attenuation of maximal senescence. As an example, the inclusion of berberine, a natural alkaloid with reported anti‐aging properties and a long history of use in traditional Chinese medicine, is shown to markedly attenuate the Mxt‐induced SI and phosphorylation of rpS6. The multivariate analysis of senescence markers by laser scanning cytometry offers a promising tool to explore the potential anti‐aging properties of a variety agents. Curr. Protoc. Cytom . 69:9.47.1‐9.47.10. © 2014 by John Wiley & Sons, Inc.